Infrared Photography: Untuk Pemasyarakatan Arkeologi - Sugeng Riyanto (Berkala Arkeologi, 2006)
The scope of public archaeology is indeed very broad, but the focus remains the same, namely how to 'spoil' the public for archaeological interests. Spoiling the public means also presenting various information generated by archaeologists according to their needs, in accordance with the developing framework and interests, including when the public is having a trend in "abnormal" photographic artwork that is infrared photography.